2018
DOI: 10.1097/pec.0000000000001442
|View full text |Cite
|
Sign up to set email alerts
|

Quality of the Triage of Children With Anaphylaxis at the Emergency Department

Abstract: Objective Early recognition of symptoms is essential in anaphylaxis management. The Canadian Paediatric Emergency Triage and Acuity Scale prioritizes anaphylaxis to level I or II (resuscitation or emergency). We analyzed the accuracy of pediatric anaphylaxis triage. Methods This was a retrospective review of the triage charts (adaptation of the Canadian Paediatric Emergency Triage and Acuity Scale) of 137 children attended for anaphylaxis at our pediatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Our study shows that less than half of the patients presenting with symptoms evocative of anaphylaxis received a high-priority code, similarly to what happened in a Spanish PED where, among 137 children referred for anaphylaxis, only 56 (33%) were triaged correctly [ 14 ]. However, the Canadian Pediatric Emergency Triage Acuity Scale [ 15 ] suggests that anaphylaxis should be prioritized to level I or II (resuscitation or emergency) and highlights how current triage, which is based on severity perception, has the limit to under-evaluate most of these cases, thus delaying treatment [ 14 ]. Another paper by the same Spanish group investigated the impact of a specific educational intervention (a training lecture to PED triage nurses and design of a reference card highlighting symptoms and risk factors for anaphylaxis).…”
Section: Discussionmentioning
confidence: 57%
“…Our study shows that less than half of the patients presenting with symptoms evocative of anaphylaxis received a high-priority code, similarly to what happened in a Spanish PED where, among 137 children referred for anaphylaxis, only 56 (33%) were triaged correctly [ 14 ]. However, the Canadian Pediatric Emergency Triage Acuity Scale [ 15 ] suggests that anaphylaxis should be prioritized to level I or II (resuscitation or emergency) and highlights how current triage, which is based on severity perception, has the limit to under-evaluate most of these cases, thus delaying treatment [ 14 ]. Another paper by the same Spanish group investigated the impact of a specific educational intervention (a training lecture to PED triage nurses and design of a reference card highlighting symptoms and risk factors for anaphylaxis).…”
Section: Discussionmentioning
confidence: 57%
“…Previously, we evaluated how our system prioritized children attended for anaphylaxis in the PEU, noting that 66% were underprioritized and thus experienced delays in receiving their treatment [10]. Other authors have reported similar results [11].…”
Section: Introductionmentioning
confidence: 78%
“…However, isolated analysis of referred patients showed no differences in the final priority level assigned: 41.7% in G1 and 52.2% in G2 were prioritized correctly (not shown in the Table). We recently analyzed how our hospital's triage system classified a group of children who were subsequently diagnosed with anaphylaxis [10] and found that 66% were undertriaged and that this delayed their medical care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations